Cultivating teacher renewal : guarding against stress and burnout - Larrivee, Barbara (Rowman & Littlefield Education, 2012)
Teachers today are more stressed than ever. It is crucial that teachers develop the tools necessary to keep from falling prey to the potentially destructive effects of stress and burnout. Cultivating Teacher Renewal: Guarding Against Stress and Burnout offers the antidote by providing the knowledge, skills and practices that will keep teachers from surrendering to burnout.